Turkish Adult Risk Factor Study survey 2012: overall and coronary mortality and trends in the prevalence of metabolic syndrome - Altan Onat; Murat Yüksel; Bayram Köroğlu; H. Ali Gümrükçüoğlu; Mesut Aydın; H. Altuğ Çakmak; Ahmet Karagöz; Günay Can (KARE Publishing, 2013)
Objectives: We aimed to analyze 1) overall and coronary mortality findings in the Turkish Adult Risk Factor (TARF) study survey 2012 and 2) the temporal trends in prevalence of metabolic syndrome (MetS) and its distribution across seven geographic regions. Study design: Information on the mode of death was obtained from first-degree relatives and/or health personnel of a local health office. Information collected in survivors was based on history, physical examination of the cardiovascular system and Minnesota coding of resting electrocardiograms. Results: Of 1527 participants to be surveyed, 796 were examined; information was obtained on the health status in 502 subjects, and death was ascertained in 56 participants. Thirty deaths were attributed to coronary and cerebrovascular disease. Cumulative 22-year evaluation of participants in the age bracket 45-74 years revealed coronary mortality to be high, with 7.6 per 1000 person-years in men and 3.8 in women. Data used from 1754 identical subjects (median age 46 years initially), and examined in two periods 12 years apart, indicated an increase in the prevalence of MetS by 1.3% per aging of 1 year. Analysis across geographic regions showed a rise in the prevalence in the Mediterranean region, already having highest prevalence along with Southeast Anatolia, while the prevalence declined in the Marmara region and persisted to be lowest in the Aegean region. Conclusion: The prevalence of MetS in Turkish adults aged 40 years or over, currently standing at 53%, shows significant differences across geographic regions, being highest in the two southern regions and lowest in the Aegean region.